Penggunaan Pil Penunda Haid Bagi Jama’ah Haji dan Umrah: Studi Komparasi Pandangan Yusuf al-Qaradawi dan Ibn Utsaimin - Mahendra, Aditya; Mustafa, Zulhas'ari; Jamil (Universitas Islam Negeri Alauddin Makassar, 2022)
This thesis discusses the Use of Menstrual Delay Pills for Hajj and Umrah Pilgrims (Comparative Study Between the Views of Yusuf al-Qardawi and Ibn Utsaimin). As for the formulation of this problem, namely (1) How is it legal to consume drugs to delay menstruation for women who carry out Hajj and Umrah? (2) What are the views of Yusuf al-Qardawi and Ibn Utsaimin regarding the use of menstrual delay pills for women who perform Hajj and Umrah? (3) The type of research is library research which is known as (Library Research) because the data being researched are books, journals, manuscripts which are all from the library. The type of data used is qualitative data type, namely the type of data related to data in the form of written words, observable events and behaviors. The results of this study are how then Yusuf al-Qardawi the pilgrims for Hajj and Umrah are allowed to consume drugs to delay menstruation in carrying out the pilgrimage and Umrah with the aim of being able to do the pillars of Hajj and Umrah perfectly without any obstacles and no problems. Because basically everything is permissible, as long as there is no prohibition from the Shari'ah. Meanwhile, al-'Utsaimin was more judgmental in terms of harm, so he suggested to those who use the drug to delay menstruation, it is better not to use it than harm in the future that befalls him.